2005
DOI: 10.1159/000089412
|View full text |Cite
|
Sign up to set email alerts
|

Personal Factors Involved in Onset or Progression of Ménière’s Disease and Low-Tone Sensorineural Hearing Loss

Abstract: Purpose: To identify personal causative factors for Ménière’s disease. Procedures: Patterns of hearing loss progression were studied in patients with Ménière’s disease and low-tone sensorineural hearing loss, and the involvement of stress and the relation of stressors to the onset or progression of the disease were analyzed. Results: Low-tone loss recurred in 40% of patients even after hearing was restored, and low-tone loss progressed to high-tone loss after frequent repetitions of recovery and recurrence. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 43 publications
(37 reference statements)
1
19
0
Order By: Relevance
“…Therefore, the good prognosis of hearing associated with the early intervention may not be due to the treatment with osmotic diuretic. On the other hand, in the present study, patients with Ménière's disease also received the instruction to operate changes in their lifestyle, especially to avoid mental and physical stress, because Ménière's disease is recognized as a stress-induced disease [7]. Indeed, it has been reported that counseling is more effective in improving the hearing level in patients with Ménière's disease than drug treatment [19], suggesting that it decreases levels of stress hormones such as vasopressin, which increases the extent of endolymphatic hydrops [20].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Therefore, the good prognosis of hearing associated with the early intervention may not be due to the treatment with osmotic diuretic. On the other hand, in the present study, patients with Ménière's disease also received the instruction to operate changes in their lifestyle, especially to avoid mental and physical stress, because Ménière's disease is recognized as a stress-induced disease [7]. Indeed, it has been reported that counseling is more effective in improving the hearing level in patients with Ménière's disease than drug treatment [19], suggesting that it decreases levels of stress hormones such as vasopressin, which increases the extent of endolymphatic hydrops [20].…”
Section: Discussionmentioning
confidence: 89%
“…It is suggested that the deteriorated hearing loss at the initial visit at middle to high frequencies is a factor of poor prognosis of the hearing loss in patients with Ménière's disease, because the hearing loss at low frequencies is fluctuating and reversible at the early stage of the disease [5] and that at high frequencies tends to be irreversible and progressive [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire used to evaluate three categories related to stress is shown in Table 2. The category dealing with personality types contained 14 items related to the type A personality (questions 1-14), five items related to the self-resistant type personality (questions [15][16][17][18][19], and five items related to the escape type personality (questions [20][21][22][23][24]. One of three responses could be chosen for each item and the score was based on the answer chosen: no (0), sometimes (1), or yes (2).…”
Section: Questionnairementioning
confidence: 99%
“…We evaluated the three personality types, means of relaxation, and causes of anxiety [18][19][20] using our questionnaire to verify the relationship between the personalities and chronic stress.…”
Section: Introductionmentioning
confidence: 99%